2021
DOI: 10.3390/biom11081206
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Biased Expression of Pharmacogenes across Human Tissues

Abstract: Individual response to drugs is highly variable and largely influenced by genetic variants and gene-expression profiles. In addition, it has been shown that response to drugs is strongly sex-dependent, both in terms of efficacy and toxicity. To expand current knowledge on sex differences in the expression of genes relevant for drug response, we generated a catalogue of differentially expressed human transcripts encoded by 289 genes in 41 human tissues from 838 adult individuals of the Genotype-Tissue Expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Recently, cardiac simulations showed that models integrating male-based data underestimated the risk for lethal arrhythmias, such as Torsade de Pointes, in females[18]. To aid the comprehensive preclinical analysis of drug action, transcriptional and other relevant data need to be viewed in a stratified manner, with considerations of the target demographics, including sex[6]. In the current study, we show several distinct sex-dependent patterns of regulation of histone modifiers and their action on cardiac ion channels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, cardiac simulations showed that models integrating male-based data underestimated the risk for lethal arrhythmias, such as Torsade de Pointes, in females[18]. To aid the comprehensive preclinical analysis of drug action, transcriptional and other relevant data need to be viewed in a stratified manner, with considerations of the target demographics, including sex[6]. In the current study, we show several distinct sex-dependent patterns of regulation of histone modifiers and their action on cardiac ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomics data can be linked to subject's demographics and other characteristics, and molecular relationships can be parsed by sex, age, tissue context and other characteristics. Now, these resources are being leveraged to estimate safety risk for drugs and to predict the outcomes of clinical trials [4][5][6], in hopes to reduce cost, time for drug development and potential side effects. Such analyses using the GTEx data have brought awareness to tissue specificity [1], cell specificity [7] and the impact of sex on key molecular pathways and transcriptional control mechanisms [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomics data can be linked to subject's demographics and other characteristics, and molecular relationships can be parsed by sex, age, and tissue context. Now, these resources are being leveraged to estimate safety risk for drugs and to predict the outcomes of clinical trials (4)(5)(6), in hopes to reduce cost, time for drug development and potential side effects. Such analyses using the GTEx data have brought awareness to tissue specificity (1), cell specificity (7) and the impact of sex on key molecular pathways and transcriptional control mechanisms (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal effects are now believed to only partially explain sex differences in these functional responses, as the GTEx data analysis has revealed that about 37% of all genes (majority of these autosomal) exhibit sex-differential gene expression in at least one tissue, including in the LV of the heart, where over 1,300 genes have differential sex expression (7). Importantly, among the most sex-differentially expressed genes are those involved in ion transport processes and response to drugs, including ion channels and CYP enzymes (6,7,19). Furthermore, sex differences in gene expression in the heart (8,9,20) include differences in the expression of epigenetic modifiers, in chromatin accessibility and the related regulatory networks (21,22).…”
Section: Introductionmentioning
confidence: 99%